The Effect Of Peer-Tutoring Method On Social Acceptance And Self-Esteem Of Individuals With Intellectual Disabilities - (:unkn) unknown (HACETTEPE UNIV, 2018)
The purposes of this study are to examine how the information-giving meetings (in separated environment) and workshops in which students with intellectual disabilities teach a skill to their typically developing peers, affect the social acceptance level of typically developing students toward students with intellectual disabilities and whether the self -esteem scores of students with intellectual disabilities differ according to the attendance to the workshop activity (as a tutor peer). This research was conducted in Istanbul with 7th and 8th grade students in a secondary school and students with intellectual disabilities of a special education center. The participants of this study are 25 students with intellectual disability and 105 trically developing students. Workshop and information-giving activities which had been developed by researchers were conducted with the students of the experimental group. The activities used in this study consist of workshop activities which were applied in 3 different days and 2 sessions of information-giving activity on the same day. In the study, pre-test/post-test control grouped experimental design is used. The research data were gathered with Social Acceptance Scale and Piers-Harris Children's Self-Concept Scale, and were analyzed with SPSS 17 program. The results from the data analysis revealed that workshop activities which were held with typically developing students had a positive effect on enhancing the social acceptance of typically developing students toward their peers with intellectual disabilities. Furthermore results from the data analysis showed that, self-esteem scores of students with intellectual disabilities did not differ according to the participation to workshop activities.
Keywords: Individual with intellectual disabilities; social acceptance; self-esteem; peer tutoring; CHILDRENS ATTITUDES; STUDENTS; INTERVENTION; COMPETENCE; KNOWLEDGE; SCHOOL